Company Complexity and Audit Delay: The Moderating Effect of Audit Committee Chair Accounting Expertise - Alisa, Inayah Risqi; Rusvina, Eva (International Journal of Digital Marketing Science, 2025)
This study aims to analyze the influence of company complexity on audit delay and the moderating effect of audit committee chair accounting expertise. The object of this study is the sector of property and real estate companies listed on the Indonesia Stock Exchange (BEI) for the 2018–2022 period. Based on the purposive sampling used, there were 34 companies that met the criteria. The analysis technique used is PLS-SEM using WarpPLS 8.0. This study shows that company complexity has a positive and significant effect on the audit delay. The higher the company complexity of its subsidiary, the higher the audit delay can be. Furthermore, the audit committee chair accounting expertise variable mitigates this effect. Previous research did not examine the role of audit committee chair accounting expertise in the complex situation that related to the higher audit delay. Theoretically, this research contributes to the study of agency theory. Practically, this research is useful for companies to monitor their audit process within the company through audit committee chairs who have accounting expertise that can reduce the length of the audit delay and complete their duties more effectively and in a timely manner.